Analisis teknik edukasi untuk meningkatkan keterampilan bantuan hidup dasar pada orang awam: A literature review - Mulyati, Pipit Sri; Melastuti, Erna; Wahyuningsih, Indah Sri; Rochmati, Dwi Heppy (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Basic Life Support (BLS) skills play a crucial role in emergency situations, such as sudden cardiac arrest and accidents, where timely and appropriate first aid can save lives. Although public awareness of the importance of BLS has increased, many laypeople still lack adequate knowledge and practical skills to perform BLS effectively. Purpose: To formulate effective educational techniques to improve basic life support skills in the general public. Method: A literature review was conducted by searching articles from Scopus, PubMed, and Google Scholar databases using a combination of keywords such as